Application of Artificial Intelligence in Cattle Farming: A Scope Review - Vitória Souza de Oliveira Nascimento, Gilmar de Oliveira Pinheiro (Revista Electronica de Veterinaria, 2022)
Cattle farming started in this country with the arrival of cattle brought in the colonial period and since then it has grown and become highly importante both economically and socially. Currently, it is noticeable evident that the advancement of technology and its application in cattle raising has the potential to make livestock even more promising. Therefore, the purpose of this article is to analyze various applications of the technology in cattle raising through a scope review. Database searches were performed and 20 studies that met the inclusion criteria were analyzed and used in the review. These studies are divided into 8 main themes, and in general a very diversified number of variables, technologies and algorithms were used. It was possible to conclude that machine learning approaches are increasingly being studied, tested and considered as a viable and promising approach for cattle raising in several aspects.